Pengaruh Financial Behavior, Financial Literacy, Financial Technology Terhadap Keputusan Berinvestasi Gen Z - Rahmi Restianti; Dwi Putra Buana Sakti; Embun Suryani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
investment decisions with financial technology as a moderating variable. The type of research conducted in this research is quantitative with purposive sampling technique. The population and sample in this study were Generation Z in Indonesia. The data method used in this study was a questionnaire method via google form. The data analysis used in this study is moderated regression analysis (MRA) using SPSS. The results show that financial literacy and financial behavior have a positive effect on investment decisions, while financial technology as a moderating variable does not have a positive effect on these two variables